The Interpretation of the Verse of Qiwāmah from the Perspective of Muhammad Sa'id Ramadhān al-Būthī: An Analysis of the Book Al-Mar'ah bain Thughyān al-Nidzām al-Gharbiy wa Lathā'if al-Tasyri' al-Rabbaniy - Fitriyah, Zakiyatul (Sophist : Jurnal Sosial Politik Kajian Islam dan Tafsir, 2024)
This paper discusses the leadership relations between men and women in Islam, especially in the context of qiwāmah based on the views of Muhammad Sa'id Ramadhān al-Būthī in the book al-Mar'ah bain Thughyān al-Nidzām al-Gharbiy wa Lathā'if al-Tasyri' al-Rabbaniy. The purpose of this study is to examine in depth the meaning of qiwāmah according to al-Būthī and how this concept is applied in the relationship between husband and wife. This study uses a qualitative method by analysing the main text of the book, as well as other literature related to the issue of qiwāmah. With a moderate and comprehensive tafsir approach, al-Būthī interprets 'qiwāmah' as the husband's responsibility to protect and nurture the family, not domination over the wife. The husband's leadership is based on his physical advantages and his role as breadwinner, but without demeaning the wife. In essence, wives still have the right to work and contribute economically as long as the work does not burden them.